Technology in teacher planning from a Universal Design for Learning: a case study of inclusive practices : Technology in teacher planning from a Universal Design for Learning: a case study of inclusive practices - García Campos, María Dolores; Canabal, Cristina (Revista Complutense de Educación, 2026)
Educational purposes are evident from the planning itself, so it must be the object of study, especially given its relevance in the generation of inclusive contexts. This paper aims to identify the use of technology in didactic planning developed under the Universal Design for Learning approach. A case study was carried out based on the analysis of nine didactic designs developed by active teachers and student teachers, who had received specific training in UDL. The content analysis revealed that technology is used to connect with the interests of the students, as well as to promote understanding through interaction with digital content, predominantly visual. However, its use is limited in facilitating action and expression of learning. The conclusions highlight the need to expand the use of technology through incorporating assistance tools and configuration options that adapt to the diversity of the student body; promoting multisensory support and decoding of information; to promote communication and the personal and collaborative construction of knowledge. Along with this, the development of learning strategies must be supported and the means to strengthen the emotional dimension and commitment must be diversified.